2022
DOI: 10.1155/2022/5260608
|View full text |Cite|
|
Sign up to set email alerts
|

miR-18a-5p and ATM Expression in Esophageal Squamous Cell Carcinoma and Their Correlations with Clinicopathological Features

Abstract: Objective. To investigate miR-18a-5p and ataxia telangiectasia muted (ATM) expression in esophageal squamous cell carcinoma (ESCC) and their correlations with clinicopathological features. Methods. The subjects of this study were 62 ESCC patients (research group, RG) and 57 healthy controls (control group, CG) presented to our hospital between July 2019 and April 2020. Peripheral blood (PB) miR-18a-5p and ATM levels in these participants were quantified via qRT-PCR, and the correlations of the two genes with E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The ROC analysis indicated that miRNAs’ sensitivity and specificity as peripheral blood-based biomarkers was 80.7% and 71.9%, respectively. Moreover, the authors have emphasized the promising prognostic and therapeutic potential of the interplay between miR-18a-5p and ATM in ESCC [ 61 ]. A different molecule that might be helpful in ESCC diagnosis is miR-20b-5p.…”
Section: Mirnas Potential — Biomarkers or Therapeutic Targets?mentioning
confidence: 99%
“…The ROC analysis indicated that miRNAs’ sensitivity and specificity as peripheral blood-based biomarkers was 80.7% and 71.9%, respectively. Moreover, the authors have emphasized the promising prognostic and therapeutic potential of the interplay between miR-18a-5p and ATM in ESCC [ 61 ]. A different molecule that might be helpful in ESCC diagnosis is miR-20b-5p.…”
Section: Mirnas Potential — Biomarkers or Therapeutic Targets?mentioning
confidence: 99%
“…This article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%